ADMINISTRATIVE OFFENSE (MISDEED) - ITS CAUSES AND PREVENTION - Butenko, Artem (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the research is a scientific analysis of the conceptual apparatus in the context of the stated problem, clarification of issues related to administrative delictology, prevention of illegal actions that fall under the definition of administrative offenses (misdeed). The methodological basis of the work is a comprehensive approach to the study of the conceptual apparatus in administrative delictology, prevention of administrative offenses (misdeed). Its basis is the dialectical method of research, as well as the analytical, comparison, and historism method, which ensure the identification of the inner essence of phenomena through the characterization of the dynamics of their development and external manifestations. The results: the relevance of the study of issues related to administrative offenses (misdeed) is related to the need to understand their content, reasons for their commission and prevention, as well as the need to improve the current legislation in this area in accordance with modern trends in the development of legislation in Ukraine. Discussion: in addition to the scientific significance, as well as the possibilities of application in the educational process of this article, it should be pointed out its relevance in relation to the law-making and legislative process. The practical significance of the article is that it provides an opportunity to orient legal doctrine to the needs of practice. When studying delict determinants, it is important to take into account the existing connections that arise between the cause and the result. The study of the problem of causal relations in administrative tort has certain limits. They determine the mutual influence of various forms of social relations and people with their individual characteristics. This fully applies to administrative tort, because it is part of the general interrelationships that are manifested in the general system of social phenomena. It will be a relief from this point of view that administrative tort as a phenomenon is regulated by administrative legislation and on the basis of existing administrative practice categories of classification and systematization have been formed, concerning both illegal actions and offenders. Such a typology has developed in recent years thanks to the norms of administrative law. It reflects the real reality that exists in modern society and can serve as the basis of conditional or temporary ideas in the field of delictological research. The limits of these studies also exist in the fact that in administrative law illegal actions are defined by the object of encroachment, which, in turn, is unequal. In addition, certain categories of illegal actions and violators reveal various connections and features that require a versatile approach and analysis of the laws of administrative tort in the context of general connections, within the limits established by administrative legislation. In the modern period of development of an independent, legal and social state in Ukraine, the problem of prevention of administrative offenses (misdeed) has become very acute. This problem is discussed in scientific circles of scientists, criminologists, philosophers, practical employees, law enforcement agencies, and, first of all, employees of the Ministry of Internal Affairs, who are responsible for the main work in this direction. The main direction in the activity of the state to fight against administrative offenses (misdeed) was, is and will be their prevention.